A ira na Hecyra de Terêncio - Silva, Stefanie Cavalcanti de Lima (2018)
The present work proposes to investigate anger in Hecyra (160 BC), play by Terence (185-159 BC), through a Stoic reading. The delimitation of analysis corpus stems from a significant recurrence of a lexical field linked to the anger notion (ira, iniuria, iniquitas) in the play, especially in episodes that involve the senes Laques and Fidipo. Judging the possibility to examine the presence of anger in Hecyra by a Stoic prism, our aim is to analyze the play in light of Theory of the Passions. To reach this goal, we elaborate a bibliographical research and then study philosophical texts that discuss the Theory of the Passions, mainly in the light of stoicism, then apply the results obtained to our research hypothesis and make a more reasoned analysis of Terence‘s text. To develop this research, we use as theoretical foundation, especially philosophical works, that discuss the Theory of Passions, especially Anger, such as Rhetorica and Ethica Nicomachea, by Aristotle, Tusculanae disputationes, by Cicero, and De ira by Seneca. In addition to ancient texts, we also use modern studies concerning the theory of passions, such as Martha C. Nussbaum and Margareth Graver. In the Introduction section, we comment on the relationship between theater and philosophy and how this relationship was given since Menander, we contextualize Terence and his work, discuss his theater relationship with philosophy, and his presence in the Scipionic Circle; in the following chapter, we present the theory of passions, the conception of anger in both peripatetic and stoic schools; in the third chapter, we analyze the presence of a lexicon linked to the notion of anger in Hecyra in the light of Stoicism. We hope, at the end of this investigation, to discover a little more on the dialogue of literature with philosophy and theater by Terence, in particular Hecyra.